The entrepreneurial personality : a social construction - Chell, Elizabeth (Hove, East Sussex ; New York : Routledge, 2008)
"This second edition of the highly acclaimed The Entrepreneurial Personality carefully weaves together the arguments and views from economists, sociologists and psychologists in order to develop a strong conceptual foundation. It discusses the inferences that these experts have made about the nature of entrepreneurs and the entrepreneurial process, and explores whether such evidence has enabled psychometricians to develop robust instruments for assessing the characteristics of entrepreneurs, Throughout, Chell laces her argument richly with a set of cases derived from primary and secondary sources." "This book presents a timely set of views on the entrepreneurial personality, and will be of great interest to academics in the fields of entrepreneurship, economics, management, applied psychology and sociology. This accessible text will also appeal to the interested general reader, as well as practitioners and consultants dealing with entrepreneurs in the field."
Includes bibliographical references (p. [269]-291) and index.
aia 09/05/13
Loan
Keywords: Entrepreneurship; Small business; Entrepreneurial personality